Perancangan User Interface Web Sma Al Ma’soem dengan Metode Kansei Engineering - Kanda Muhamad Ishak (INTERNAL (Information System Journal), 2022)
Website User Interface (UI) design is an important factor in the use of design to look attractive, many things the appearance of the website is not attractive and the message you want to convey is not conveyed effectively, this is of course based on the needs and feelings of each user. This research applies the Kansei Engineering method to design a website appearance design. The method used refers to the Kansei Engineering Type 1 methodology. This research has applied Kansei Engineering to generate recommendations for website display design concepts. The kansei word list used is 20 words related to the appearance of the website. The website display specimens used were 8 specimens. This study involved 60 participants consisting of 30 class X high school students and 30 class X high school students. This research produced new design products in 2 categories, namely design products based on student participants produced the concept of "Bright" emotions for female participants to produce the concept of emotions "Colored".